The role of membrane fatty-acid transporters in regulating skeletal muscle substrate use during exercise - Pelsers, M. M. A. L.; Stellingwerff, T.; van Loon, L. J. C. (Sports Medicine, 2008)
While endogenous carbohydrates form the main substrate source during high-intensity exercise, long-chain fatty acids (LCFA) represent the main substrate source during more prolonged low- to moderate-intensity exercise. Adipose tissue lipolysis is responsible for the supply of LCFA to the contracting muscle. Once taken up by skeletal muscle tissue, LCFA can either serve as a substrate for oxidative phosphorylation or can be directed towards esterification into triacylglycerol. Myocellular uptake of LCFA comprises a complex and incompletely understood process. Although LCFA can enter the cell via passive diffusion, more recent reports indicate that LCFA uptake is tightly regulated by plasma membrane-located transport proteins (fatty acid translocase [FAT/CD36], plasmalemmal-located fatty acid binding protein [FABPpm] and fatty acid transport protein [FATP]). Depending on cardiac and skeletal muscle energy demands, some of these LCFA transporters can translocate rapidly from intracellular pools to the plasma membrane to allow greater LCFA uptake. This translocation process can be induced by insulin and/or muscle contraction. However, the precise signalling pathways responsible for activating the translocation machinery remain to be elucidated. This article will provide an overview on the effects of diet, acute exercise and exercise training on the expression and/or translocation of the various LCFA transporters in skeletal muscle tissue (FAT/CD36, FABPpm, FATP).